Confined growth of small ZnO nanoparticles in a nitrogen-rich carbon framework: Advanced anodes for long-life Li-ion batteries. (March 2017) - Sun, Fei; Gao, Jihui; Wu, Haobin; Liu, Xin; Wang, Lijie; Pi, Xinxin; Lu, Yunfeng
Abstract: Commercialization of ZnO-based anodes remains hampered by their rapid capacity fading upon cyclical charge and discharge. Design and synthesis of suitable carbon scaffolds for coating ZnO active materials has been regarded as the most effective strategy to overcome this problem. We herein report a confined growth strategy for the synthesis of a novel ZnO/carbon mesoporous composite that consists of small ZnO nanoparticles whose growth is confined in rationally designed N-rich carbon spheres (referred to as ZnO-NMPCS). Such a mesoporous nanocomposite has several structural merits such as small ZnO nanoparticles, a homogeneous distribution, an interconnected spherical framework with a large surface area, and a N-rich carbon lattice; these merits not only provide a robust scaffold for stable lithiation/delithiation of ZnO active materials but also ensure sufficient Li + storage space/sites and fast ions/electrons transport. As a result, the developed nanocomposite exhibits excellent Li + storage properties in terms of high capacity, fast rate capability, and long cycling lifespan (425 mAh g −1 after 1800 cycles at 5 A g −1 ). This work offers an effective confined growth strategy to overcome the long-term roadblock to ZnO-based anodes; the carbon scaffold also provides a general platform for the confined growth of other metal oxide nanocrystals. Graphical abstract: